Peran LPMK dan BKM Dalam Pemberdayaan Masyarakat Di Kecamatan Tembalang - Ridwan Dannar D; Wiwik Widayati; Ahmad Taufiq (Journal of Politic and Government Studies, 2013)
ABSTRACTThe study of the Community Empowerment By LPMK and BKM in DistrictTembalang an interesting study along with the development efforts and the efforts to improve thewelfare of society. Empowerment as the process develops, to be independent, to be self-help,1 Mahasiswa Ilmu Pemerintahan FISIP UNDIP 20082 Dosen Ilmu Pemerintahan FISIP UNDIP3 Dosen Ilmu Pemerintahan FISIP UNDIP2strengthen the bargaining position of the lower layers of society against oppressive powerstrength in all areas and sectors of life. The essence of empowerment is a strategy to leverage thepower and independence of the community. Community empowerment at the village area ofSemarang district by LPMK (Institute for Village Empowerment) and BKM (Agency forCommunity Self-Reliance). LPMK oriented to empowering all people through the development /improvement of infrastructure neighborhoods. While BKM oriented towards empowerment ofthe poor.The result of this research are as follows. First, empowerment programs in the SubDistrict Tembalang done by LPMK (Institute for Village Empowerment) and BKM (Agency forCommunity Self-reliance) through three aspects: social aspects, environmental aspects,economic aspects and followed communities in need. Secondly, the provision of capital toexisting systems and processes group sharing between agencies beneficiaries withempowerment. Third, these institutions have a business as a source of income which is then usedfor the implementation of community development programs. Fourth, the empowerment programinvolves renovation of uninhabitable housing, construction of arthesian wells, making pavingroads and providing scholarships to poor students. Fifth, this empowerment has a pattern andwell capitalized. Sixth, lack of socialization by the government.Keywords: empowerment_LPMK_BKM